The Purpose of Islamic Education in Kitab Al-Uṣûl aṡ-Ṡalâṡah by Shaîkh Muhammad At-Tamîmiy - Syahrul Holid; Syamsu Nahar; Azizah Hanum OK (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This study aims to determine the purpose of Islamic education in the book Al-Uṣûl aṡ-Ṡalâṡah by Shaîkh Muhammad At-Tamîmiy. The research method uses qualitative methods that are descriptive with the type of library research. The main source of this research is a scholarly book entitled Al-Uṣûl aṡ-Ṡalâṡah wa Adillatuhâ. Based on the results of research shows that the main purpose of Islamic education formulated by Shaîkh Muhammad At-Tamîmiy in his book is inseparable from three basic things, namely that Islamic education aims to make students know Allah Almighty (ma'rifatullâh), know the Prophet (ma'rifatu nabiyyihî), and know Islam and its postulates (ma'rifatu dîn al-islâm bi al-adillah). These three goals are the foundation for all the goals of Islamic education built upon it. Through the knowledge of Allah Almighty, learners will know the consequences of the creed lâ ilâha illallâh and the purpose of its creation, as well as know Allah's rights over His servant and the servant's duty to His Rabb. Through the introduction of His Prophet, learners will know the consequences of the creed of Muhammad rasulullâh. Through the introduction of Islam and its postulates, students will know the nature of their religious teachings which are built on scientific divine values.